External field effect on the anisotropy of dielectric permeability of KH₂PO₄ and NaKC₄H4O₆· 4H₂O crystals under high pressure - Slivka, A.G.; Kedyulich, V.M.; Guyvan, H.M. (Condensed Matter Physics, 2008)
Experimental studies of the effect of temperature, external pressure and electric eld on the anisotropy of
dielectric permeability of KH₂PO₄ and NaKC₄H4O₆· 4H₂O crystals are performed. The experimental data
on the effect of electric field and pressure on the dielectric permeability of Rochelle salt are analyzed in the
framework of phenomenological theory with the account of the vicinity of the phase transitions to the double
critical point. Coefficients of thermodynamic potential expansion over the order parameter are determined as
well as its pressure behaviour is described. The hydrostatic pressure increase is shown to shift the phase
transitions in Rochelle salt away from the double critical point. Проведено експериментальнi дослiдження впливу температури, зовнiшнього тиску та електричного поля на анiзотропiю дiелектричної проникностi кристалiв KH₂PO₄ та NaKC₄H4O₆· 4H₂O. У рамках феноменологiчної теорiї та з врахуванням близькостi фазових переходiв до подвiйної критичної точки проведено аналiз експериментальних результатiв по впливу електричного поля та тиску на дiелектричну проникнiсть сегнетової солi. Визначено коефiцiєнти розкладу термодинамiчного потенцiалу по параметру порядку i їх баричну поведiнку. Показано, що збiльшення гiдростатичного тиску вiддаляє фазовi переходи в сегнетовiй солi вiд подвiйної критичної точки.